Learning Strategies at During the Covid-19 Pandemic at SD Muhammadiyah 5 Porong - Dwi Febyanovi Inaya; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This research examines various aspects, including: student learning activities, problems during learning, to learning solutions at SD Muhammadiyah 5 Porong in the midst of the Covid-19 pandemic. In the research process using data collection techniques by means of interview, observation, photos and videos when the research process was carried out. This study aims to obtain information regarding the strategies being carried out at SD Muhammadiyah 5 Porong in learning in the midst of the Covid-19 pandemic. This research method uses descriptive qualitative research methods. The existence of the Covid-19 pandemic has resulted in the teaching and learning process now being shifted to online learning. Online learning is a solution to solving educational problems due to the current Covid-19 pandemic. The offline method is also applied through face-to-face learning and continues to carry out obligations by complying with health protocols. Such is the learning conducted at SD Muhammadiyah 5 Porong. By using the online method and the offline method which is applied at SD Muhammadiyah 5 Porong amidst the current learning problems with the state of Indonesia affected by Covid-19.